2015
DOI: 10.4103/0976-3147.158755
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica and neuromyelitis optica spectrum disorder: Natural history and long-term outcome, an Indian experience

Abstract: Background:Neuromyelitis optica (NMO) has evolved from devic's classical description to a broader disease spectrum, from monophasic illness to a polyphasic illness with multiple recurrences, disease confined to optic nerve and spinal cord to now brain stem, cerebrum and even endocrinopathy due to hypothalamic involvement.Objectives:To report, the epidemiological characteristics, clinical presentations, recurrence rate, treatment and response to therapy in 26 patients with NMO and NMO spectrum disorder among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
2
14
1
1
Order By: Relevance
“…The authors confirmed a strong female preponderance for NMO/NMOSD. [ 8 ] However, women/men ratio in this study was lower compared to a recent paper on the Indian NMO/NMOSD cohort,[ 7 ] (female: male = 4.2:1 and 7.8:1, respectively), but higher in the monophasic than in the polyphasic form (6:1 and 3.75:1, respectively),[ 8 ] in contrast to previous literature data. [ 1 ]…”
contrasting
confidence: 94%
See 3 more Smart Citations
“…The authors confirmed a strong female preponderance for NMO/NMOSD. [ 8 ] However, women/men ratio in this study was lower compared to a recent paper on the Indian NMO/NMOSD cohort,[ 7 ] (female: male = 4.2:1 and 7.8:1, respectively), but higher in the monophasic than in the polyphasic form (6:1 and 3.75:1, respectively),[ 8 ] in contrast to previous literature data. [ 1 ]…”
contrasting
confidence: 94%
“…Among 83 recurrent events, ON was found in 23%, LETM in 56.62%, both ON and LETM in 16.9% of polyphasic patients, being these data similar to those reported in a recent work on an Indian NMO/NMOSD cohort. [ 7 ] Even the median number of relapses was similar in both studies: 4 (range: 2–8) during a mean follow-up of 5 years in the former,[ 8 ] and 3 (range: 1–15) during a median follow-up of 3 years (range: 0.33–30 years) in the latter. [ 7 ] Moreover, the mean age of symptom onset of 27 years (range: 9–58) found in this study is similar to that median of 26.5 (range: 8–72) of a previous Indian study,[ 7 ] but it is lower than that reported in previous studies performed in American and Western countries,[ 1 4 ] suggesting that NMO/NMOSD cases in Indian population might tend to present at an earlier age.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Adicionalmente, outros pontos vêm ganhando atenção ampliando assim o espectro da caracterização dos episódios de neuromielite óptica. Notadamente, o curso monofásico da doença, a qual se atribui frequência de 5% a 10% (Wingerchuk et al, 2015), embora na Índia tenha frequência ainda superior, 27% (Jagtap et al, 2015).…”
Section: -unclassified